Reactive nodular fibrous pseudotumor: A rare mesenchymal tumor - Krishna, M Sunil; Todi, Richa; Shenoy, K. Rajgopal; Bhat, Chitra Y; Kumar, M Keerthan (Indian Journal of Case Reports, 2019)
Reactive nodular fibrous pseudotumor (RNFP) is a recently described non-neoplastic mesenchymal lesion arising from thegastrointestinal tract, mesentery, or retroperitoneum. It is a rare entity with only a few cases reported in literature so far and is lessaggressive when compared to other mesenchymal lesions such as gastrointestinal stromal tumor (GIST) or fibromatosis. Here, wepresent the case of a 20-year-old female who presented with a huge abdominal mass. Contrast-enhanced computed tomographywas suggestive of pseudopapillary tumor of the pancreas. The patient underwent exploratory laparotomy and excision of the massin toto along with sleeve gastrectomy and splenectomy. Post-operative histopathology confirmed the entity to be RNFP. This caseillustrates the need for keeping RNFP in mind as a differential diagnosis in a case of large abdominal mass as it has a fairly goodprognosis with no reported recurrence after surgical excision.